1999
DOI: 10.1149/1.1392524
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performance of Amorphous and Crystalline Sn2 P 2 O 7 Anodes in Secondary Lithium Batteries

Abstract: In 1994, Fuji Photo Film Co., Ltd., Japan, filed a patent for nonaqueous Li-ion batteries in which tin composite oxides (TCOs) were used as the active anode material. 1 Since then, much attention has been given to the potential of substituting this class of compounds for carbon negative electrodes in Li-ion batteries. Tin oxide composites are attractive because of their high gravimetric and volumetric specific capacities relative to carbon, which enable cells of higher energy densities to be built. 2 It is rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 8 publications
4
74
2
Order By: Relevance
“…Hence, the reversible anode peaks at ∼0.35 V and cathode peaks at ∼0.15 V in the differential capacity plots for both glasses are related to the lithium insertion and extraction reactions, respectively, associated with alloying and de-alloying of Li-Ge phases. On the other hand, the irreversible sharp cathodic peaks observed on the first cycle curves are associated with the decomposition of the GeX 2 Similar results are also observed in the TCO glasses [28,29].…”
Section: Electrochemical Properties Of Ges 2 Glasssupporting
confidence: 64%
See 1 more Smart Citation
“…Hence, the reversible anode peaks at ∼0.35 V and cathode peaks at ∼0.15 V in the differential capacity plots for both glasses are related to the lithium insertion and extraction reactions, respectively, associated with alloying and de-alloying of Li-Ge phases. On the other hand, the irreversible sharp cathodic peaks observed on the first cycle curves are associated with the decomposition of the GeX 2 Similar results are also observed in the TCO glasses [28,29].…”
Section: Electrochemical Properties Of Ges 2 Glasssupporting
confidence: 64%
“…This is superior not only to that of GeO 2 glasses (Fig. 5), but also to that previously reported for the TCO glasses [4][5][6]28,29]. Similar to the case of GeO 2 glass, there are no distinctive XRD patterns found during the discharging and charging process of GeS 2 glass.…”
Section: Electrochemical Properties Of Ges 2 Glasssupporting
confidence: 58%
“…Sn 0 ) and Li 2 Obased glassy matrix (irreversible process), and the second plateau is due to the formation of Li-Sn alloy domains (Sn 0 ? Li-Sn) (reversible process) [35][36][37].…”
Section: All-solid-state Batteries Using the LI 2 S-p 2 S 5 Glassceramentioning
confidence: 99%
“…Tin-oxide-based glasses [19,20] were reported to work as a negative electrode material with high capacity in lithium ion cells. The cell performance of SnO-based glasses exhibited larger reversible capacity than the corresponding crystalline material [21]. We have also developed a series of SnO-based borate, phosphate, and borophosphate glasses [22,23] and found that the capacity of the cells using these active materials depended on the composition of glasses, and was closely related to local structure of the glasses.…”
Section: Construction Of All-solid-state Cells With a Variety Of Actimentioning
confidence: 99%
“…On the basis of the mechanism of electrochemical lithium insertion to SnObased glassy materials [20][21][22], the first plateau on the charge curve of the cell with the 80SnS·20P 2 S 5 electrode in Fig. 4 is probably due to the formation of metallic Sn nanoparticles and Li 2 S P 2 S 5 glassy matrix (irreversible process), and the second plateau is due to the formation of Li Sn alloy domains (reversible process).…”
Section: Construction Of All-solid-state Cells With a Variety Of Actimentioning
confidence: 99%